Ablation of IGFBP5 expression alleviates neurogenic erectile dysfunction by inducing neurovascular regeneration - Jiyeon Ock; Guo Nan Yin; Fang-Yuan Liu; Yan Huang; Fitri Rahma Fridayana; Minh Nhat Vo; Ji-Kan Ryu (Investigative and Clinical Urology)
"Purpose: To investigate the therapeutic potential of eliminating insulin-like growth factor-binding protein 5 (IGFBP5) expression in improving erectile function in mice with cavernous nerve injury (CNI)-induced erectile dysfunction (ED). Materials and Methods: Eight-week-old male C57BL/6 mice were divided into four groups: a sham-operated group and three CNI-induced ED groups. The CNI-induced ED groups were treated with intracavernous injections 3 days before the CNI procedure. These injections included phosphate-buffered saline, scrambled control short hairpin RNA (shRNA), or shRNA targeting mouse IGFBP5 lentiviral particles. One week after CNI, erectile function was evaluated and the penile tissue was then harvested for histological examination and western blot analysis. Additionally, the major pelvic ganglia (MPG) and dorsal root ganglia (DRG) were cultured for ex vivo neurite outgrowth assays. Results: Following CNI, IGFBP5 expression in the cavernous tissues significantly increased, reaching its peak at day 7. First, ablation of IGFBP5 expression promotes neurite sprouting in MPG and DRG when exposed to lipopolysaccharide. Second, ablating IGFBP5 expression in CNI-induced ED mice improved erectile function, likely owing to increased neurovascular contents, including endothelial cells, pericytes, and neuronal processes. Third, ablating IGFBP5 expression in CNI-induced ED mice promoted neurovascular regeneration by increasing cell proliferation, reducing apoptosis, and decreasing Reactive oxygen species production. Finally, western blot analysis demonstrated that IGFBP5 ablation attenuated the JNK/c-Jun signaling pathway, activated the PI3K/AKT signaling pathway, and increased vascular endothelial growth factor and neurotrophic factor expression. Conclusions: Ablating IGFBP5 expression enhanced neurovascular regeneration and ultimately improved erectile function in CNI-induced ED mice."